Is there enough evidence for osteosarcopenic obesity as a distinct entity?: a critical literature review - Bauer, Jürgen M. (Calcified tissue international, 2019)
The co-existence of impaired bone health (osteopenia/osteoporosis), reduced muscle mass and strength (sarcopenia), and increased adiposity (obesity) in middle-aged and older people has been identified in recent studies, leading to a proposal for the existence of “osteosarcopenic obesity” as a distinct entity. Evidence for the pathophysiological overlap of these conditions is mounting, although a causal relationship is yet to be established. Each component condition occurs frequently with increasing age, and with shared risk factors in many instances, thus, an overlap of these three conditions is not surprising. However, whether the concurrent existence of sarcopenia, osteoporosis and obesity leads to an increased risk of adverse musculoskeletal outcomes and mortality above and beyond the risks associated with the sum of the component parts remains to be proven and is a question of research interest. In this article, we review evidence for the existence of osteosarcopenic obesity including the current operational definition of osteosarcopenic obesity, prevalence, pathophysiology, outcomes and exploratory approaches to the management of components. We conclude that, there is insufficient evidence to support a discrete clinical entity of osteosarcopenic obesity at this time. To expand knowledge and understanding in this area, there is a need for consensus on a definition of osteosarcopenic obesity which will allow for identification, further epidemiological studies and comparisons between studies. Additionally, studies should assess whether the clinical outcomes associated with osteosarcopenic obesity are worse than the mere addition of those linked with its components. This will help to determine whether defining a person as having this triad will eventually result in a more effective treatment than addressing each of the three conditions separately.
Gesehen am 06.02.2020
Received: 26 September 2018